Preventative Control of Brown Patch with Select Fungicides - E. Alderman; J. Reeves; J. Hoyle (Kansas Agricultural Experiment Station Research Reports, 2016)
Preventative applications of Velista and Heritage Action fungicides will decrease the percentage of brown patch observed in a perennial stand of tall fescue.
Keywords: turfgrass; disease; Brown Patch